Electrophoretic deposition of (Cu, Mn, Co)3O4 spinel coating on SUS430 ferritic stainless steel: Process and performance evaluation for solid oxide fuel cell interconnect applications. Issue 2 (February 2021) - Aznam, Isyraf; Mah, Joelle C.W.; Muchtar, Andanastuti; Somalu, Mahendra R.; Ghazali, Mariyam J.
Highlights: Detailed study on the effects of suspension stability and particle mobility for EPD. A uniform and dense spinel coating with good adhesion to SUS430 was produced. The spinel coating reduced the oxidation kinetic by three orders of magnitude. Electrical conductivity of spinel-coated SUS430 is sufficient for SOFC applications. The chemically stable (Cu, Mn, Co)3O4 coating effectively inhibits Cr migration. Abstract: This study aimed to investigate the colloidal stability of (Cu, Mn, Co)3 O4 spinel in various suspension media and suitable applied voltage for electrophoretic deposition (EPD). The performance of the coated SUS430 was evaluated in terms of oxidation behaviour, Cr migration and electrical conductivity. The (Cu, Mn, Co)3 O4 suspension prepared using a mixture of 50/50 isopropanol and acetylacetone presented the highest zeta potential (41.4 mV), which indicated a stable and well-dispersed suspension. An applied voltage of 80 V is recommended to produce a coating surface with uniform particle arrangement. The electrophoretically deposited (Cu, Mn, Co)3 O4 spinel coating could reduce the oxidation kinetics by three orders of magnitude and exhibited stable electrical conductivity during 200 h of oxidation. Cr element was not detected on the surface of the coated SUS430 and LSCF cathode after 200 h of oxidation. Therefore, the electrophoretically deposited (Cu, Mn, Co)3 O4 spinel coating could successfully inhibit Cr migration from the stainless steel interconnects to the cathode.